The Impact of Knowledge Management on Faculty Performance A Field Study on Faculty Members at Misurata University (Economic studies journal, 2025)
This study aims to investigate the nature of the fundamental impact of knowledge management dimensions on the performance of faculty members at Misurata University, and to provide a deeper understanding of the independent variables represented by the four dimensions of knowledge management: knowledge generation, knowledge storage, knowledge distribution, and knowledge application. These objectives are achieved through a precise research methodology, starting with verifying the existence of a statistically significant effect for each of the four dimensions of knowledge management. The study relied on the descriptive analytical approach, as data were collected through a field survey using a questionnaire specifically designed for this purpose. The questionnaire was distributed to a random sample of 320 individuals representing the study population of approximately (1200) individuals, ensuring a broad representation of the academic reality. Advanced statistical analyses conducted using SPSS yielded substantive results, revealing a positive, strong, and statistically significant impact of the combined knowledge management dimensions on the overall performance of faculty members at Misurata University. These empirical results confirm that investing in knowledge management processes is not merely an administrative choice; Rather, it is a strategic necessity for improving academic performance. It also confirms that improving knowledge management practices leads to a significant improvement in academic performance.Based on these conclusions, the study presents a set of practical and concrete recommendations. It emphasizes the development of an integrated strategic approach to knowledge management and the need to formulate institutional strategies to enhance knowledge storage and distribution mechanisms, invest in knowledge-supporting infrastructure, motivate faculty members to generate quality knowledge, and establish a knowledge-based organizational culture. It also emphasizes the importance of integrating all dimensions of knowledge management to achieve continuous improvement in academic performance. These findings can be leveraged to develop effective policies and programs that contribute to building a sustainable competitive advantage for the university, enhancing its position as a leading academic institution
Keywords: Knowledge management; knowledge generation; knowledge storage; knowledge distribution; knowledge application; faculty performance